MEMAHAMI PERSONAL BRANDING BERDASARKAN THE BIG FIVE PERSONALITY TRAITS (STUDI PADA ANGKATAN KERJA SMK) - Sania , Sania; P. Tommy Y. S. , Suyasa (Provitae: Jurnal Psikologi Pendidikan, 2024)
The purpose of this research is to understand the effectiveness of personal branding based on the concept of the bigfive personality traits, which act as predictors of self-image among vocational high school students. Personalbranding is the process of creating, positioning, and maintaining a positive self-image, which is increasingly relevantin today’s educational and professional environments, especially for vocational high school students. Personalitytraits which reflect individual’s beliefs and tendencies in behavior, are crucial in shaping personal branding. In thisstudy, the subjects consist of 100 students from SMK X in Tangerang City. Data were collected through an e-surveyusing two main instruments: Personal Brand Equity (PBE; Gorbatov et al., 2020), which measures three dimensionsof personal branding—brand appeal, brand differentiation, and brand recognition —and an adaptation of the NEOPersonality Inventory (NEO-PI-R; Costa & McCrae, 1992), which measures five dimensions of personality traits—neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness. Based on the analysis usingSpearman’s Correlation Test, the results are as follows: (a) personal branding cannot be predicted by the neuroticismdimension of the personality traits; (b) personal branding can be partially predicted (brand appeal and branddifferentiation dimensions) by the openness to experience dimension of the personality traits; and (c) personalbranding can be predicted as a whole (brand appeal, brand differentiation, and brand recognition dimensions) by theextraversion, agreeableness, and conscientiousness dimensions of the personality traits. The results of this study havesignificant implications for educational institutions and companies in assisting vocational high school students indeveloping their personal branding.